The Role of Selenium Nanoparticles in Addressing Diabetic Complications: A Comprehensive Study - Satpathy, Siddharth; Panigrahi, Lipsa Leena; Arakha, Manoranjan (Current Topics in Medicinal Chemistry, 2024)
Diabetes, as an emerging epidemic, has put forward a significant spotlight on the evolving population worldwide grounded upon the remarkable affliction of healthcare along with economical conflict. Various studies suggested that, in modern society, lack of maintenance of a healthy life style leads to the occurrence of diabetes as insulin resistant, later having a damaging effect on the pancreatic β-cells, suggesting various complications. Furthermore, diabetes management is controversial owing to different opinions based on the prevention of complications. For this purpose, nanostructured materials (NSM) like selenium nanoparticles (SeNPs) have proved their efficiency in the therapeutic management of such serious diseases. This review offers an in- 3:27 PM 6/4/2024depth idea regarding the pathophysiology, diagnosis and various conventional therapeutics of type 1 and type 2 diabetes, shedding light on Diabetic Nephropathy (DN), a case study of type 1 diabetes. Moreover, this review provides an exhaustive study by highlighting the economic and healthcare burdens associated with diabetes along with the controversies associated with conventional therapeutic management and the promising role of NSM like selenium nanoparticles (SeNPs), as a novel weapon for encountering such fatal diseases.
Keywords: Diabetes